MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI SENI MELIPAT ORIGAMI PADA ANAK KELOMPOK B RAUDATUL JANNAH - Musafir, Musafir; Hadi, Rusman; Muhajirin, Muhammad (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to improve fine motor skills through the art of folding origami in children aged 5-6 years. The subjects in this study were group B with 15 students, consisting of 6 male students and 9 female students. This type of research is Classroom Action Research (CAR) which is carried out and ends in a cycle that achieves the specified learning outcomes. The data collection instrument used observation, interviews, and documentation. Data analysis uses quantitative data. The results showed that the art of folding origami could improve children's fine motor skills. This can be seen from the research data, namely in Cycle I 60% or 9 students from the total number of children in the BSH category, while in Cycle II there was an increase to 80% or 12 students from the total number of children in the class, 9 students. students are in the BSH category while the other 4 students are in the BSB category. This shows that the use of the art of folding origami effectively improves children's fine motor skills at the early childhood education level.